The Miltonic Moment - Evans, J. Martin (John Martin), 1935-2013 (Book collections on Project MUSE., 1998)
Milton's poems invariably depict the decisive instant in a story, a moment of crisis that takes place just before the action undergoes a dramatic change of course. Such instants look backward to a past that is about to be superseded or repudiated and forward, at the same time, to a future that will immediately begin to unfold. Martin Evans identifies this moment of transition as ""the Miltonic Moment."" This provocative new study focuses primarily on three of Milton's best known early poems: ""On the Morning of Christ's Nativity, "" ""A Mask Presented at Ludlow Castle (Comus), "" and ""Lycidas."